Applications and Potentials of Intelligent Swarms for magnetospheric studies. (April 2022) - Rajan, Raj Thilak; Ben-Maor, Shoshana; Kaderali, Shaziana; Turner, Calum; Milhim, Mohammed; Melograna, Catrina; Haken, Dawn; Paul, Gary; Vedant,; Sreekumar, V.; Weppler, Johannes; Gumulya, Yosephine; et al.
Abstract: Earth's magnetosphere is vital for today's technologically dependent society. To date, numerous design studies have been conducted and over a dozen science missions have flown to study the magnetosphere. However, a majority of these solutions relied on large monolithic satellites, which limited the spatial resolution of these investigations, as did the technological limitations of the past. To counter these limitations, we propose the use of a satellite swarm carrying numerous and distributed payloads for magnetospheric measurements. Our mission is named APIS — Applications and Potentials of Intelligent Swarms. The APIS mission aims to characterize fundamental plasma processes in the Earth's magnetosphere and measure the effect of the solar wind on our magnetosphere. We propose a swarm of 40 CubeSats in two highly-elliptical orbits around the Earth, which perform radio tomography in the magnetotail at 8–12 Earth Radii ( R E ) downstream, and the subsolar magnetosphere at 8–12 R E upstream. These maps will be made at both low-resolutions (at 0.5 R E, 5 s cadence) and high-resolutions (at 0.025 R E, 2 s cadence). In addition, in-situ measurements of the magnetic and electric fields, plasma density will be performed by on-board instruments. In this article, we present an outline of previous missions and designs for magnetospheric studies, along with the science drivers and motivation for the APIS mission. Furthermore, preliminary design results are included to show the feasibility of such a mission. The science requirements drive the APIS mission design, the mission operation and the system requirements. In addition to the various science payloads, critical subsystems of the satellites are investigated e.g., navigation, communication, processing and power systems. Our preliminary investigation on the mass, power and link budgets indicate that the mission could be realized using Commercial Off-the-Shelf (COTS) technologies and with homogeneous CubeSats, each with a 12U form factor. We summarize our findings, along with the potential next steps to strengthen our design study. Highlights: We present an overview of science drivers, previous design studies and space missions for magnetospheric studies. We present a satellite swarm concept to characterize the plasma processes and study the effect of the solar wind on our Magnetosphere. The swarm of 40 CubeSats will perform both in-situ measurements, and radio tomography in the magnetotail at 8–12 Earth Radii. We investigate various critical subsystems of the satellite, with a focus on navigation, communication and processing. Our preliminary investigations indicate that the satellite could be realized using a 12U CubeSat from COTS technologies.